Diagnostic Utility of Cell Population Data (CPD) In Sepsis Using Automated Hematology Analysers - P, Shalini; Rao, Purnima S; A R, Sneha Rao; Anil, Manjula; Benny, Athira; I, Sandhya (Annals of Pathology and Laboratory Medicine, 2019)
Background: Sepsis still remains an important cause of morbidity and mortality posing a diagnostic challenge to clinicians across the globe. Lack of a single specific and sensitive test paved the way to many researches. Our study evaluated clinical significance of cell population data (CPD) as biomarkers in sepsis. CPD assesses morphological and functional characteristics of leucocytes using automated hematology analyzer. Methods: The study population consisted of 100 healthy subjects and 100 clinically suspected cases of sepsis with quick sequential organ failure assessment (qSOFA) score >2. The various cell population data (CPD) were collected using automated hematology analyzer, Sysmex XN1000 during a span of 6 months from January to June 2018 in a tertiary care center and the results were statistically analyzed using Z test. Result: The WBC count and CPD parameters were assessed. Except for neutrophil , monocyte cell size (NE-FSC, MO-Z) and lymphocyte fluorescence intensity(LY-Y) all other CPD parameters show significant difference (p<0.001) in sepsis group compared to healthy controls. Conclusion: This study suggested utility of CPD parameters which provide details of size and internal structure of leucocytes to be considered as an important biomarker for diagnosis and management of sepsis.